2013
DOI: 10.4236/ojog.2013.31a036
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte quality improvement using a herbal medicine comprising 7 crude drugs

Abstract: Maternal age is a significant factor in infertility treatment. Ovarian function and oocyte quality decrease with age, whereas the frequency of chromosomal abnormalities increases. In this study, improvement of oocyte quality and ovarian function were attempted using a herbal medicine comprising 7 crude drugs: Angelicae radix, Rehmanniae radix, Plantaginis semen, Lonicerae flos, Carthami flos, Ginseng radix, and Cucurbita moschata Duch. Thirty-one women who repeatedly failed to conceive by intracytoplasmic sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The procedure involves surgically removing eggs from a woman's ovaries, combining them with sperm in the laboratory, and returning them to the woman's body or donating them to another woman [32]. Herbal medicine may use as an adjunct to ART in women by an improvement in oocyte quality [20,33] and ovarian function [33]. A study by Ushiroyama T, Yokoyama N [20] found that macrophageactivating Chinese mixed herbs (MACH) were safe in improving ISSN: 2581-3846 the reproductive outcomes in patients who had previously failed ART due to low embryonic quality.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure involves surgically removing eggs from a woman's ovaries, combining them with sperm in the laboratory, and returning them to the woman's body or donating them to another woman [32]. Herbal medicine may use as an adjunct to ART in women by an improvement in oocyte quality [20,33] and ovarian function [33]. A study by Ushiroyama T, Yokoyama N [20] found that macrophageactivating Chinese mixed herbs (MACH) were safe in improving ISSN: 2581-3846 the reproductive outcomes in patients who had previously failed ART due to low embryonic quality.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, long, short, or gonadotropin-releasing hormone (GnRH)-antagonist protocols were used depending on the patient. In poor responders who have ≤2 follicles even if they were injected with human menopausal gonadotropin (hMG; ASKA Pharmaceutical Co., Tokyo, Japan) several times before during previous infertility treatment, including timing treatment or artificial insemination with sperm from the patient's husband, in combination with herbal medicine, clomifene citrate (50 mg Spacromin tablet, Pola Pharma Inc., Tokyo, Japan) and hMG were used for ovarian stimulation [ 20 ]. A GnRH analogue acetate (Fuji Pharma Co., Tokyo, Japan), hMG, and a GnRH antagonist (Cetrotide, Shionogi & Co., Osaka, Japan) were used in each protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Oocytes were inseminated by IVF or ICSI. ICSI was performed as described previously [16]. In brief, spermatozoa were selected by hyaluronic acid (HA).…”
Section: Ovarian Stimulation/in Vitro Fertilisation/intracytoplasmicsmentioning
confidence: 99%